2005
DOI: 10.1088/0022-3727/38/21/r01
|View full text |Cite
|
Sign up to set email alerts
|

A review and outlook for an anomaly of scanning tunnelling microscopy (STM): superlattices on graphite

Abstract: Since its invention in 1981, scanning tunnelling microscopy (STM) is well-known for its supreme imaging resolution enabling one to observe atomic-scale structures, which has led to the flourishing of nanoscience. As successful as it is, there still remain phenomena which are observed using STM but are beyond our understanding. Graphite is one of the surfaces which have been most extensively studied using STM. However, there are a number of unusual properties of graphite surfaces. First reported in the 1980s, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
128
1
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(144 citation statements)
references
References 92 publications
(243 reference statements)
11
128
1
4
Order By: Relevance
“…For intermediate angles (1 15 ), it is predicted that, while the linear dispersion persists in the vicinity of the Dirac points of both layers, the band velocity is depressed and two saddle points appear in the band structure, giving rise to two logarithmic van Hove singularities (vHs) in the density of states (DOS) [9,[13][14][15][16][17][18]. For smaller angles ( 1 ) weakly dispersive bands appear at low energy [19,20] with sharp DOS peaks very close to the Dirac point [17,18].Twisted graphene layers are commonly found on different substrates, such as metals [13,21,22], the C face of SiC [23][24][25], or graphite surfaces [26,27]. Transfer techniques yielding large domains of twisted bilayers over a macroscopic sample [28] and quantitative, fast, Raman characterization tools [29,30] have recently been proposed.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…For intermediate angles (1 15 ), it is predicted that, while the linear dispersion persists in the vicinity of the Dirac points of both layers, the band velocity is depressed and two saddle points appear in the band structure, giving rise to two logarithmic van Hove singularities (vHs) in the density of states (DOS) [9,[13][14][15][16][17][18]. For smaller angles ( 1 ) weakly dispersive bands appear at low energy [19,20] with sharp DOS peaks very close to the Dirac point [17,18].Twisted graphene layers are commonly found on different substrates, such as metals [13,21,22], the C face of SiC [23][24][25], or graphite surfaces [26,27]. Transfer techniques yielding large domains of twisted bilayers over a macroscopic sample [28] and quantitative, fast, Raman characterization tools [29,30] have recently been proposed.…”
mentioning
confidence: 99%
“…Twisted graphene layers are commonly found on different substrates, such as metals [13,21,22], the C face of SiC [23][24][25], or graphite surfaces [26,27]. Transfer techniques yielding large domains of twisted bilayers over a macroscopic sample [28] and quantitative, fast, Raman characterization tools [29,30] have recently been proposed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bernal-stacked graphene shows quadratic energymomentum dispersion due to strong interlayer interaction and a bandgap opening due to symmetry breaking. Twisted graphene (TG) rotated by an arbitrary angle is commonly found in graphene grown on metals 3,9,10 , C-face SiC 11 or bulk graphite surfaces 12,13 , and is still under intensive study to identify its properties. Ab initio calculations showed that the Dirac cones and Fermi velocity of each layer preserved those of SLG due to decoupling between layers 14 .…”
mentioning
confidence: 99%
“…However, imaging depth of optical microscopy has been fundamentally limited to millimeter or sub-millimeter due to multiple scattering of light in a biological sample. Conventional microscopy techniques utilize visible light or electron sources [12][13][14]. Optical microscopy divides into transmission (i.e., wide-field microscopies for snap-shot of 2D images in terms of light absorption, phase contrast, or dark-field signals) and emission modes (i.e., wide-field fluorescence microscopy, confocal laser scanning microscopy, and two-photon fluorescence microscopy).…”
Section: Introductionmentioning
confidence: 99%